2020
DOI: 10.3390/w12051494
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Radar-Gauge Merging Techniques to Be Used in Operational Flood Forecasting in Urban Watersheds

Abstract: Demand for radar Quantitative Precipitation Estimates (QPEs) as precipitation forcing to hydrological models in operational flood forecasting has increased in the recent past. It is practically impossible to get error-free QPEs due to the intrinsic limitations of weather radar as a precipitation measurement tool. Adjusting radar QPEs with gauge observations by combining their advantages while minimizing their weaknesses increases the accuracy and reliability of radar QPEs. This study deploys several techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 97 publications
1
4
0
Order By: Relevance
“…At the scale of urban hydrology applications, the role of measurement biases is particularly important since the high-intensity/short-duration events producing the most relevant urban floods are also the most affected by instrumental sources of error. This is confirmed in the paper by Wijayarathne et al [12], where the performance of all methods used are shown to deteriorate with increasing the severity of rainfall events.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…At the scale of urban hydrology applications, the role of measurement biases is particularly important since the high-intensity/short-duration events producing the most relevant urban floods are also the most affected by instrumental sources of error. This is confirmed in the paper by Wijayarathne et al [12], where the performance of all methods used are shown to deteriorate with increasing the severity of rainfall events.…”
supporting
confidence: 63%
“…As a third example of the impact of measurement accuracy on the hydrological applications, Wijayarathne et al [12] contribute a study of radar-gauge merging techniques for use in operational flood forecasting in urban watersheds. Indeed, after adjusting radar estimates with gauge observations by combining their advantages while minimizing their weaknesses, the authors manage to increase their accuracy and reliability.…”
mentioning
confidence: 99%
“…Different methodologies of applying areal precipitation may also affect the final rain distribution per sub-watershed. In a recent study regarding the Humber River basin, various radar-gauge merging techniques were applied to ensure optimum rainfall evaluation [67]. In this research paper, we proposed certain values of parameters regarding two applied hydrological models for precipitation events with different characteristics that decision-makers and policy planners should take into account to adapt to the consequences of future extreme events, especially in the residential areas towards the basin's outlet.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have presented different techniques for accomplishing this data merging task for rainfall map production [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%